ECSCW 2007 Proceedings of the 10th European Conference on Computer-Supported Cooperative Work, Limerick, Ireland, 24-28 September 2007 - Bannon, Liam J.; Wagner, Ina; Gutwin, Carl; Harper, Richard H.R; Schmidt, Kjeld (Springer London : Imprint: Springer, 2007)
This volume presents the proceedings of the tenth European conference on Computer Supported Cooperative Work (CSCW). This is a multidisciplinary area that embraces the development of new technologies grounded in actual cooperative practices. These proceedings contain a collection of papers that reflects the breadth and depth of research activities in this field. The volume includes papers addressing novel interaction technologies for CSCW systems, new models and architectures for groupware systems, studies of communication and coordination among mobile actors, studies of cooperative work in complex settings, studies of groupware systems in actual use in real-world settings, and theories and techniques to support the development of cooperative applications. The papers present emerging technologies alongside new methods and approaches to the development of this important class of applications. The work in this volume provides a snapshot of the current state of research and practice within CSCW. The collection of papers presented here will appeal to researchers and practitioners alike, as they combine an understanding of the nature of work with the possibilities offered by new technologies.